PENGEMBANGAN MUJARAB (MU’JAM JAWA-ARAB) SEBAGAI PENUNJANG KETERAMPILAN BERBICARA BAHASA ARAB SISWA SMA DI PATI - Inarotud Dujja; Nailur Rahmawati (Lisanul Arab: Journal of Arabic Learning and Teaching, 2023)
Mujarab (Javanese-Arabic Dictionary) is a website-based online thematic dictionaryused to support the Arabic speaking skills of Senior High School students.This research was motivated by problems in Senior High School students inPati who still have difficulty in learning Arabic, especially in speaking skills. Thisdifficulty is caused by the lack of vocabulary mastered by students. One of the mediathat can be used to increase student vocabulary is a dictionary. Then researchersdeveloped a website-based online thematic dictionary called "Mujarab" using twolanguages, namely Javanese and Arabic. Javanese was chosen because Javanese isthe language of instruction in learning. In addition, the Javanese language serves asa preservation of Javanese culture and as a medium for instilling character andpoliteness values towards students. The problems studied in this study are: 1) How toanalyze the needs of Mujarab development, 2) How to design Mujarab, 3) and Howto validate experts and teachers against Mujarab. This research uses a qualitativeapproach with research and development (R&D) design. The research model uses theADDIE model without using the implementation stage. The subjects of the studywere teachers and grade X students at MA Sunan Prawoto and SMA Muhammadiyah3 Kayen with sample selection techniques using purposive sampling techniques, anddata collection techniques using interviews, questionnaires, and documentation. Theresults of this research are: 1) Teachers and students want the development ofMujarab; 2) This efficacious design has several features, namely Homepage,vocabulary, expressions; dialogues, exercises, aphorisms, exercises, instructions, andprofiles; 3) The assessment of Mujarab in the aspect of language and materialfeasibility obtained an average score of 45,4, while in the media aspect obtained anaverage score of 43.2. The total average score of Mujarab is 88,6 with a very decentcategory, so it can be used as a medium in learning Arabic speaking skills of grade XSenior High School students. 4) Mujarab improvements by experts include: colorselection on media as a product differentiator, icon changes on the "Home" menu inMujarab, improvements to inappropriate images, improvements to impropergrammar, changes in word diction in Javanese vocabulary, changes in image size,uniformity of font types on each page, and changes in the order of the Mujarabfeatures.